Parking tickets and police reform: an analysis of the development and impact of police scandals - Mulcahy, Aogán (Policing and society, 2021)
While police scandals are often assumed to arise from major forms of misconduct, here I argue that minor or banal events can also precipitate scandals and mobilise significant reform initiatives. My argument is based on a case-study analysis of two scandals surrounding allegations of misconduct in relation to road traffic policing in Ireland. The first case involved allegations that ‘fixed charges notices’ (issued for various driving offences) were cancelled inappropriately. The second case emerged from disclosures surrounding the vast over-counting of the number of roadside breath-tests conducted by police officers. Although these events may appear banal at first glance, they had an enormous effect on the policing landscape. Drawing on analysis of the numerous inquiries and investigations into these events, I suggest that the impact of scandal is amplified when two factors are present. First, the scandal surrounding an issue grows when it serves as a catalyst, adding to the momentum of other concerns. Second, a scandal is also magnified when it raises systemic concerns that extend beyond any individual misconduct and call into question basic features of organisational competence and legitimacy.